Utility of blood lactate level in triage. Issue 2 (17th August 2015) - Fukumoto, Yuichi; Inoue, Yoshiaki; Takeuchi, Yuji; Hoshino, Tetsuya; Nakamura, Yuki; Ishikawa, Kohei; Morikawa, Miki; Suginaka, Hiroshi; Sueyoshi, Koichiro; Sumi, Yuka; Matsuda, Shigeru; Okamoto, Ken; et al.
Abstract : Aim: Simple Triage and Rapid Treatment (START) is commonly used at disaster scenes. The Canadian Emergency Department Triage and Acuity Scale (CTAS) is used in urban and rural emergency departments (ED). However, triage is not always accurate or appropriate. The blood lactate level (BLL) is a major biomarker of physical status. We measured BLL using the Lactate Pro‐1710 Test Meter in all patients transported to our ED and assessed their correlation with the triage level determined using START and the CTAS. Methods: This retrospective study included 510 patients admitted to our ED between January 2011 and July 2012 whose BLL was measured. The patients were classified into triage divisions (green, yellow, red, and black) according to vital signs and chief complaints, and correlations among BLL, triage level, and prognosis were assessed in all groups. Results: Of the total, 62 patients had cardiopulmonary arrest (CPA), 262 had internal pathologies, and 186 had external pathologies. Significant correlations were observed between BLL and both START and CTAS triage. Also BLL was significantly higher in severe patients categorized with START and CTAS ( P < 0.0001), especially in the death group when the patients were divided into two groups according to prognosis ( P < 0.0001). Two patients categorized yellow with START died during the hospitalization, however BLL of these two patients were high on admission at the ED. Conclusion: BLL could be used to correct the triage level, and decide the priority of treatment and transportation even within the same triage level, thereby avoiding under‐triage.